A SOUND FROM THE “ARA NESİL”: MEHMED CELAL'S STORIES ON LOVE DISEASE / MANIFOLD VIEWS - Nazlı MEMİŞ BAYTİMUR (Fırat University, 2019)
It is called as “Ara Nesil” the group partaking between the second generation of Tanzimat period and Servet-i Fünun. This group that has been mentioned first time by Mehmet Kaplan and in the next times this group has been adopted by the other researchers. But there is a dimness about the historical frame of the Ara Nesil and members of this group. The reason of this dimness is that there is not a common publication organ of the Ara Nesil specialists. Moreover this group have not a certain literal understanding. But this condition does not change the truth that the Ara Nesil has continued its activities from 1880’s until 1900’s years and the members of this group have written poems, novels, stories, critiques, essays and translations. Mehmet Celal is one of the important delegates of the Ara Nesil. He has written many works like poem, novel, translation ect. At the same time he has shouldered single-handed the development mission of story kind in the period as both quality and quantity. According to our determination Mehmet Celal has 84 compilation stories. This is a great success for the writer at a time when the story line has just begun to find itself. These stories have been shaped on love theme. Sometimes love becomes an obsession and this condition affects the person as negative. The feeling which is sensed as love by person transforms an illness in time and this condition waftes the person to the tragedy. The other damaging aspects of love are extreme jealousy and drink dependency.